The determination of heavy metals in bananas - Chow, Ow Wei (Universiti Malaysia Sarawak (UNIMAS), 1998)
The contents of eight heavy metals, which are arsenic, lead, copper, tin, zinc, mercury, cadmium and antimony, in 2 species of banana was determined using the Inductively Coupled Plasma - Atomic Emission Spectrometric method. Among the analysed species are Musa sp. cv. Embun and Musa sp. cv. Hotel. From the results, the levels of heavy metals were generally below the permissible levels of heavy metal as stipulated in the Food Act, 1983 (Act 281) and Malaysian Food Regulations, 1985. The results also indicated that the eoncentrations of tin in the fruits were significantly higher than other metallic elements. Heavy metal constituents in the soil where thE! fruits were cultivated were also determined. Soil organic matter and the soil pH were investigated in order to correlate with heavy metal contents in the bananas. The results also implied a low degree of contamination in the plantation area.